Pattern visual evoked potentials in hyperthyroidism. Issue 7 (July 1988) - Mitchell, K W; Wood, C M; Howe, J W
Abstract : Pattern reversal visual evoked potentials (VEPs) have been elicited in 16 female hyperthyroid patients before and after treatment and compared with those from a similar group of age and sex matched control subjects. No effect on latency was seen, and although larger amplitude values were noted in the thyrotoxic group these too were not significant. We would conclude that hyperthyroidism per se has little effect on the pattern reversal VEP, and any observed effect on these potentials is probably due to other factors.